Body Mass Index and the Risk of Rheumatoid Arthritis: An Updated Dose-Response Meta-Analysis. (2nd July 2019) - Feng, Xia; Xu, Xizhu; Shi, Yanjun; Liu, Xuezhen; Liu, Huamin; Hou, Haifeng; Ji, Long; Li, Yuejin; Wang, Wei; Wang, Youxin; Li, Dong
Abstract : Background . Extensive studies have been carried out to investigate the association between obesity and the risk of rheumatoid arthritis (RA); however, the results of the current reported original studies remain inconsistent. This study aimed to clarify the relationship between body mass index and rheumatoid arthritis by conducting an updated overall and dose-response meta-analysis. Methods . The relevant literature was searched using the PubMed and Embase databases (through 20 September 2018) to identify all eligible published studies. Random-effect models and dose-response meta-analyses were used to estimate the pooled risk ratio (RR) with a 95% confidence interval (CI). Subgroup analyses were also conducted based on the characteristics of the participants. Sensitivity analyses and publication bias tests were also performed to explore potential heterogeneity and bias in the meta-analysis. Results . Sixteen studies that included a total of 406, 584 participants were included in the meta-analysis. Compared to participants with normal weight, the pooled RRs of rheumatoid arthritis were 1.12 (95% CI, 1.04-1.20) in overweight and 1.23 (95% CI, 1.09-1.39) in obese participants. There was evidence of a nonlinear relationship between body mass index (BMI) and RA ( P for nonlinearity less than 0.001 in the overall meta-analysis, P for nonlinearity=0.025 in the case-control studies, P for nonlinearity=0.0029 in the cohort studies). No significant heterogeneity was found among studies (I 2 =10.9% for overweight andI 2 =45.5% for obesity). Conclusion . The overall and dose-response meta-analysis showed that increased BMI was associated with an increased risk for rheumatoid arthritis, which might present a prevention strategy for the prevention or control of rheumatoid arthritis. The nonlinear relationship between BMI and RA might present a personal prevention strategy for RA.